THE SOCIO-ECONOMIC CHALLENGES OF INFERTILE WOMEN IN LAKSHMIPUR DISTRICT, BANGLADESH - Md Zahidul Islam; Nishat Tasnim; Md Sobur Hossain (Innovative Issues and Approaches in Social Sciences)
Previous Studies have been carried out in developed and developing countries, including the United Kingdom and the United States, on the relationship between age, socioeconomic status (SES), and infertility. However, its importance in Bangladesh has not been analyzed much. The study investigated the socio-economic challenges faced by infertile women in the Lakshmipur district of Bangladesh, using a mixed-method approach through 30 interviews, 5 focus group discussions (FGD), and a survey of 50 participants. Quantitative results showed that 80% of infertile women reported experiencing financial difficulties, 30% reported being subjected to blame, and 26.67% reported having experienced acts of violence. The qualitative results highlight the complex effects of infertility, including gender inequality, psychological distress, social isolation, and lack of family support. Women expressed concerns about their fear of abandonment or remarriage, economic stress, and the experience of emotional and physical abuse. Gender-based expectations and different levels of support from spouses, families, and communities have significantly impacted these challenges, affecting the adaptation process and mental well-being.